Remarkable impacts of probiotics supplementation in enhancing of the antioxidant status: results of an umbrella meta-analysis - Musazadeh, Vali; Faghfouri, Amir Hossein; Zarezadeh, Meysam; Pakmehr, Azin; Moghaddam, Pooria Taghavi; Hamedi-Kalajahi, Fateme; Jahandideh, Arian; Ghoreishi, Zohreh (Frontiers in Nutrition, 2023)
Numerous meta-analyses demonstrated the beneficial effects of probiotics on oxidative stress biomarkers, although some studies have contradictory results. Therefore, current research was conducted to give a precise and definite understanding on the impact of probiotics on oxidative stress biomarkers in adults. We conducted a comprehensive systematic search of Scopus, PubMed, Embase, Web of Science, and Google Scholar up to March 2022. Fifteen meta-analyses were included in this umbrella meta-analysis. Random-effects model was employed to obtain overall effect size. Subgroup analyses were carried out based on supplementation dosage and duration, mean age and study population. Our results indicated that probiotics supplementation meaningfully decreased serum malondialdehyde (MDA) (ESWMD= -0.56, 95% CI: -0.72, -0.39; p< 0.001, and ESSMD= -0.50, 95% CI: -0.66, -0.34; p< 0.001). Also, the findings showed that probiotics resulted in a significant increase in total antioxidant capacity (TAC) (ESWMD= 29.18, 95% CI: 16.31, 42.04; p< 0.001, and ESSMD= 0.25, 95% CI: 0.02, 0.47; p= 0.032), total glutathione (GSH) (ESWMD: 30.65; 95% CI: 16.94, 44.35, p<0.001) and nitric oxide (NO) (ESWMD: 1.48; 95% CI: 0.31, 2.65, p= 0.013; I2= 51.7%, p= 0.043). Probiotics could be considered as a strong agent in reinforcement of antioxidant status and preventing incidence of chronic diseases.